Aplikasi berbasis Quick Response Code dan Framework CodeIgniter untuk Optimalisasi Transaksi Pemesanan - Budiman, Arif; Siska, Sri Tria; Alfiani, Suci (Jurnal Sains dan Teknologi (JSIT), 2024)
Daily transactions with higher volumes are a challenge for businesses, both in the service and product sectors. Accelerating the transaction process using a computer is a solution used in almost all sectors because using a computer can provide efficiency in terms of time, energy, and speed. This research aims to design a web-based application with the CodeIgniter framework and Quick Response Code (CR Code) to conduct daily transactions for small and medium-sized businesses in the culinary field. This research is devoted to the sale of drinks and food at Kopinated. This application focuses on providing an easy and simple ordering infrastructure with a modern and dynamic look using Bootstrap. This application provides an ordering menu and payments that will be integrated directly with the server on the local host of the business. With this application, it is expected to encourage the speed of transactions for food and beverage business owners who need speed in service.